Management challenges in the treatment of severe hyperbilirubinemia in low- and middle-income countries: Encouraging advancements, remaining gaps, and future opportunities - Satrom, Katherine M.; Farouk, Zubaida L.; Slusher, Tina M. (Frontiers in Pediatrics, 2023)
Neonatal jaundice (NJ) is common in newborn infants. Severe NJ (SNJ) has potentially negative neurological sequelae that are largely preventable in high resource settings if timely diagnosis and treatment are provided. Advancements in NJ care in low- and middle-income countries (LMIC) have been made over recent years, especially with respect to an emphasis on parental education about the disease and technological advancements for improved diagnosis and treatment. Challenges remain, however, due to lack of routine screening for SNJ risk factors, fragmented medical infrastructure, and lack of culturally appropriate and regionally specific treatment guidelines. This article highlights both encouraging advancements in NJ care as well as remaining gaps. Opportunities are identified for future work in eliminating the gaps in NJ care and preventing death and disability related to SNJ around the globe.